The second stage - Friedan, Betty 1921-2006 (Summit Books, 1981)
Warning the women's movement against dissolving into factionalism, male-bashing, and preoccupation with sexual and identity politics rather than bottom-line political and economic inequalities, Friedan argues that once past the initial phases of describing and working against political and economic injustices, the women's movement should focus on working with men to remake private and public arrangements that work against full lives with children for women and men both. Friedan's agenda to preserve families is far more radical than it appears, for she argues that a truly equitable preservation of marriage and family may require a reorganization of many aspects of conventional middle-class life, from the greater use of flex time and job-sharing, to company-sponsored daycare, to new home designs to permit communal housekeeping and cooking arrangements.